Vive la difference: males vs females in flies vs worms. - Cline, T.W.; Meyer, B.J. (Annual Review of Genetics, 1996)
For 600 million years, the two best-understood metazoan species, the nematode Caenorhabditis elegans and fruit fly Drosophila melanogaster, have developed independent strategies for solving a biological problem faced by essentially all metazoans: how to generate two sexes in the proper proportions. The genetic program for sexual dimorphism has been a major focus of research in these two organisms almost from the moment they were chosen for study, and it may now be the best-understood general aspect of their development. In this review, we compare and contrast the strategies used for sex determination (including dosage compensation) between "the fly" and "the worm" and the way this understanding has come about. Although no overlap has been found among the molecules used by flies and worms to achieve sex determination, striking similarities have been found in the genetic strategies used by these two species to differentiate their sexes.